Analysis of energy saving effect and cost efficiency of ECMs to upgrade the building energy code - Kim, Hye Gi; Kim, Hyun Jun; Jeon, Chae Hwan; Chae, Myeong Won; Cho, Young Hum; Kim, Sun Sook (Energies, 2020)
Building energy codes are key policy tools for improving building energy efficiency by defining the minimum requirement for the energy performance of new buildings. In Korea, the building energy code was focused on prescriptive criteria for a long time but is now gradually introducing performance criteria. However, switching to performance criteria is not straightforward because of the resistance of the market to abandoning the well-consolidated prescriptive criteria. The objective of this study is to derive appropriate measures to strengthen the prescriptive criteria and the performance criteria, considering both the energy-saving effect and the economic efficiency for new office buildings and educational buildings to increase the market acceptance of the building energy codes. To this end, the energy-saving effects of reference buildings resulting from the reinforcement of the prescriptive criteria in the past have been first analyzed. Then, based on the collected energy performance parameters and cost data, the economic efficiency relative to the energy saving deriving from the application of passive and active energy conservation measures (ECMs) were analyzed, and future building energy code’s reinforcement measures were derived.
Keywords: Building energy code; Building energy efficiency; Economic efficiency; Educational buildings; Energy-saving effect; Minimum requirements; Performance criterion; Reinforcement measures; Building energy code; Energy conservation measure; Energy saving ratio; Investment cost